The SAGE handbook of school organization - Connolly, Michael 1942-; Eddy-Spicer, David; James, Chris 1949-; Kruse, Sharon D. (SAGE Publications Ltd, 2019)
The SAGE Handbook of School Organization presents a substantial review of the history, current status and future prospects of the field of school organization. Bringing together chapters exploring key issues, important debates and points of tension, the Handbook highlights the dynamics and interplay of the political, social, historical and cultural contexts of the field. This volume is designed to provide a much-needed critically informed and coherent account of the field, against a backdrop of increasing complexity in which schooling as an institution and schools as organizations operate. Part I: Schools as organizations; Part II: The leadership, management and governance of schools as organizations; Part III: Theoretical perspectives on schools as organizations; Part IV: Organizing in schools; and Part V: Researching schools as organizations
Keywords: School management and organization -- Handbooks, manuals, etc; Leadership -- Handbooks, manuals, etc; Schulorganisation